Pemeriksaan kadar glukosa pada darah yang diperiksa segera dan ditunda selama 4, 8 dan 12 jam pada suhu kamar - Hayati, Fahra; Alsyarief, Syarifah Wahyuni; Fitriana, Fitriana; Putri, Safridha Kemala (JoMLaT (Journal of Medical Laboratory Technology), 2024)
Checking blood sugar levels is usually carried out as a screening test, diagnostic and control test. The aim of the diagnostic test is to confirm the diagnosis of Diabetes Mellitus (DM) in individuals with clinical complaints of DM. In carrying out laboratory examinations, sometimes several problems are found, so that the examination has to be postponed. Delays in examinations are one of the problems that can occur in laboratories. To determine the description of blood glucose levels in specimens that were examined immediately and delayed for 4, 8 and 12 hours with storage at room temperature. This research uses quantitative experimental research methods to determine the effect of independent variables on the dependent variable. Research results: The results of the immediate blood glucose level examination were 270 mg/dl and the results of glucose levels postponed for 4 hours were 271 mg/dl. Then, when the glucose examination was postponed for 8 hours, 262 mg/dl and 12 hours, 256 mg/dl, the glucose level decreased so that the glucose level became low. Based on research on samples of Diabetes Mellitus sufferers who were examined at the Bunda Thamrin Clinical Laboratory in Banda Aceh, it can be concluded that there was a decrease in blood glucose levels in the sample delay treatment for 8 and 12 hours at room temperature. Namely 262 mg/dl at 8 hour delay and 256 mg/dl at 12 hour delay. It is hoped that laboratory staff will always carry out examinations immediately without having to delay the examination which will cause incorrect results for patients